Offshore investors place their chips on Chinese foundries. - Jen Lin-Liu (IEEE spectrum)
Judging China an electronics superpower in the making, large corporations like Japan's NEC, as well as independent Taiwanese investors, are racing to set up semiconductor wafer fabrication lines within its territory. This paper examines how, all the same, given the overall downturn in the chip sector, some observers wonder whether this is the right time for companies to start building expensive fabs in China.